2007
DOI: 10.1590/s1519-69842007000200015
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive phenology of an herbaceous-subshrub layer of a Savannah (Campo Sujo) in the Cerrado Biosphere Reserve I, Brazil

Abstract: The objective of this study was to analyse the phenological events in the herbaceous and subshrub layer in relation to rainfall and the dispersion syndromes of the species at a Campo Sujo community in the Água Limpa Farm (FAL), Brasília-DF. Campo Sujo is a grassland Savannah with a few scattered shrubs and small trees. The climate is Aw by Köppen classification with a mean annual precipitation of 1500 mm. Herbaceus species with three to ten individuals were monitored totalling 519 individuals of 61 species. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
24
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 22 publications
9
24
0
7
Order By: Relevance
“…The predominance of anemochoric dispersion over time is associated to the physiognomic types of the sites, which are open grasslands, and the dominance of herbaceous species, a pattern observed in other studies on the Cerrado (Batalha et al 1997;Batalha and Mantovani 2000;Tannus et al 2006), and in this dry-shrub grassland seven years ago (Munhoz and Felfili 2007b), but increased zoochory may be another factor to confirm the influence of the absence of fire in the changes found in the landscape over time, especially in the ALF wet grassland, where after years of fire protection a greater density of chamaephytes and phanerophytes was verified. The prevalence of the zoochoric dispersal syndrome in different environments is associated with the dominance of woody species (phanerophytes and chamaephytes), as occurs in the cerrado sensu stricto and forest habitats (Batalha and Mantovani 2000;Kinoshita et al 2006;Tannus and Assis 2006;Ishara and Maimoni-Rodella 2011).…”
Section: Resultssupporting
confidence: 64%
“…The predominance of anemochoric dispersion over time is associated to the physiognomic types of the sites, which are open grasslands, and the dominance of herbaceous species, a pattern observed in other studies on the Cerrado (Batalha et al 1997;Batalha and Mantovani 2000;Tannus et al 2006), and in this dry-shrub grassland seven years ago (Munhoz and Felfili 2007b), but increased zoochory may be another factor to confirm the influence of the absence of fire in the changes found in the landscape over time, especially in the ALF wet grassland, where after years of fire protection a greater density of chamaephytes and phanerophytes was verified. The prevalence of the zoochoric dispersal syndrome in different environments is associated with the dominance of woody species (phanerophytes and chamaephytes), as occurs in the cerrado sensu stricto and forest habitats (Batalha and Mantovani 2000;Kinoshita et al 2006;Tannus and Assis 2006;Ishara and Maimoni-Rodella 2011).…”
Section: Resultssupporting
confidence: 64%
“…The change in the observation interval of the reproductive events (from fortnightly to bimonthly) might have subsampled the community phenological patterns, but our results agree with Munhoz and Felfili (2007) and Tannus et al (2006), which indicated a peak of flowering for the herbaceous community at the end of rainy season. In the border, the number of species with flowers and/or fruits was greater in the middle of the rainy season, therefore earlier than in savanna, that had its reproductive peak in the end of the rainy season.…”
Section: Discussionsupporting
confidence: 50%
“…The effects of burning on reproduction may be more complex though. Some studies conducted in Cerrado areas have shown that herbaceous species are able to flower and fruit shortly after fires (Coutinho, 1976;César, 1980;Munhoz and Felfili, 2007); while in a grassland in the South of Brazil, Fidelis and Blanco (2014) showed some species only reproducing more than one year after fire.…”
Section: Introductionmentioning
confidence: 99%
“…As a vegetation that is susceptible and conditioned by fire (Coutinho 1990), especially savannas and grasslands, this is another factor that can play selective pressure on fruit types in Cerrado. It has been demonstrated that fire increases nutrient cycling on soil and stimulates flowering and thus seed production in some Cerrado plants, such as Poaceae, Cyperaceae and Bromeliaceae (Munhoz & Felfili 2007), and that high temperatures caused by fire can also accelerate fruit drying and seed release and higher germinability in some species, like Kielmeyera coriacea, which have a coriaceous dry fruit (Cirne & Miranda 2008;Zaidan & Carreira 2008). However, there is still little information available about the fire effects on fruit production and germination of the Cerrado species, especially in woody plants (Palermo & Miranda 2012).…”
Section: Discussionmentioning
confidence: 99%